Pengaruh Nilai Pelanggan, Kepuasan Pelanggan dan Kepercayaan terhadap Loyalitas Pelanggan pada Kedai Kopi Online di Kota Medan - Stevani Korentia Sebayang; Syafrizal Helmi Situmorang (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2019)
The purpose of this study was to determine the influence of perceived value, customer satisfaction, and trust on online coffee shop customer loyalty in medan city. The population in this study are customer of online coffee shops in the city of Medan. The sample in this study were 150 online coffee shop customer in city of Medan who had bought online coffee priducts at least 2 times. The method of analysis used in this research is descriptive analysis method and multiple linear regression analysis processed with SPSS for windows software. Based on the F test (simultaneously) it shows that customer value, customer satisfaction and trust together or simultaneously have a significant effect on customer loyalty. The results of t-test (partial), the variable customer value has a positive and significant effect on customer loyalty, the customer satisfaction variable has a positive and significant effect on customer loyalty, and trust has a positive and significant effect on customer loyalty. Based on the large value of Adjusted Rsquare, it can be seen that the variable customer value, customer satisfaction and trust have a simultaneous effect on customer loyalty by 0.462 or 46.2% while the remaining 53.8% are other factors outside the variables studied.